Patterns of symptoms and severity of interstitial cystitis/bladder pain syndrome: a clinical analysis - Fadi Sawaqed; Mohammad Salem Hareedy; Malik Ayyad; Samer Al-Rawashdeh; Yousef M. Al‑saraireh (African Journal of Urology)
Abstract Purpose Interstitial cystitis (IC) or bladder pain syndrome (BPS) is a prevalent condition that presents the need to improve understanding of this ailment to facilitate treatment and diagnosis. However, the data regarding this syndrome is very limited for the Jordanian population. Therefore, this study was centered around assessing symptom severity and how it correlates to gender. Methods Records of 147 patients diagnosed with IC/BPS between September 2014 and June 2019 in Karak Governmental Hospital were retrieved. Demographics and symptom severity information were also obtained. SPSS version 27 was used to carry out all statistical analyses and to determine the association between gender and symptom severity. Results 80.3% of the study population comprised women, and incidence remained unaffected with increasing age. Among symptoms, only urinary frequency (p = 0.018) and weaker urine flow (p = 0.002) were influenced by gender, and severity was significantly higher in males than females. Nocturia was the only symptom affected by age-related differences (p = 0.070). The analysis also revealed a statistically significant negative correlation between gender and nocturia (ρ = −0.196, p = 0.017), as well as between gender and weak urine flow (ρ = −0.251, p = 0.002). Conclusions IC/BPS is more prevalent in women. Age and gender at large do not affect symptom severity. Correlation analysis between gender and symptoms revealed that some symptoms, such as nocturia and weak urine flow, are likely to be more severe in men.